VALIDITY AND RELIABILITY TESTING OF THE ORGANIZATIONAL COMMUNICATION SATISFACTION SCALE FOR MILLENIAL EMPLOYEES IN INDONESIA - Nugroho Dwi Priyohadi; Fendy Suhariadi; Fajrianthi Fajrianthi; Soedarmanto Soedarmanto (Journal of Educational, Health and Community Psychology, 2019)
This study aims to test and carry out the process of adapting the organizational communication satisfaction measurement tool of millennial employees in Indonesia. The purpose of this research is to discover suitable measurement of communication satisfaction, adjusted to the conditions in Indonesia. Confirmatory Factor Analysis (CFA) method with AMOS version 18 was used to analyzed data of 738  people who participated in the study from April to August  2019. The CFA model used to test the Communication Satisfaction instrument uses the second-order model consisting of seven dimensions: Communication Climate and Organizational Integration; Supervisory Communication; Media Quality; Horizontal (Coworker) Communication; Organizational Perspective (Corporate Information); Personal Feedback; Subordinate CommunicationThe scale was adapted from the Communication Satisfaction questionnaire developed by Down & Hazen (1977), Down & Adrian (2004), Okay and Okay (2009)  and Wagner et al. (2014). The results show that the scale is valid for 40  items and invalid for 1  item. It is concluded that the adaptation process was successfully carried out, and the scale could be used for millennial employees.  Keywords:Communication satisfaction, millennial employees, scale adaption, organizational performance